The Influence Of Experiential Marketing On Repurchase Intention (Study On Regular Customers Of Cargo X Telukdalam City) - Tafonao, Aluiwaauri (Maneggio, 2024)
The rapid development in the service sector also increases the difficulty, namely failure to meet customer wants and needs, reflected in the low customer buying interest in the products and services produced by the company. In the author's observation, repurchase intention on regular Cargo X customers in Telukdalam City is low. The low repurchase intention can be seen from consumers who use Cargo services from 2020 to 2023 has decreased significantly. As for repurchase intention, it is influenced by many factors, but in this study it is only focused on experiential marketing variables. This study aims to determine the effect of experiential marketing on repurchase intention on regular customers of Cargo X Telukdalam city with the sample being regular customers of Cargo X Telukdalam city in 2023 totaling 120 people. This research uses a quantitative research approach. The data analysis technique in this study uses multiple linear regression analysis whose calculations are carried out with the IBM SPSS version 21 program. The results showed that the experiential marketing variable had a positive and significant effect on repurchase intention